Partial mtDNA sequencing data of vulnerable Cephalopachus bancanus from the Malaysian Borneo - Muhamad Aidil, Zahidin; Norehan, Abd Jalil; Nur Mukminah, Naharuddin; Mohd Ridwan, Abd Rahman; Millawati, Gani; Mohd Tajuddin, Abdullah (Elsevier Inc., 2019)
Tarsier is an endangered nocturnal primate in the family Tarsiidae and is an endemic to Sundaic islands of Philippine (Carlito syrichta), Sulawesi (Tarsius tarsier-complex) and Borneo (Cephalopachus bancanus). Recent records indicated that most molecular studies were done on the Eastern Tarsier and little information for the other group of tarsiers. Here, we present a partial cytochrome b data set of C. bancanus in Sarawak, Malaysian Borneo. Standard mist nets were deployed at strategic locations in various habitat types. A total of 18 individuals were caught, measured and weighed. Approximately, 2 × 2 mm of tissue samples were taken and preserved in molecular grade alcohol. Out of 18, only 11 samples were screened with partial mtDNA (cytochrome b) and the DNA sequences were registered in the GenBank (accession numbers: KY794797-KY794807). Phylogenetic trees were constructed with 20 additional mtDNA sequences downloaded from GenBank. The data are valuable for the management authorities to regulate the type of management units for the metapopulation to sustain population genetics integrity of tarsiers in the range countries across the Sunda Shelf.